A Comprehensive Review on Graptopetalum paraguayense’s Phytochemical Profiles, Pharmacological Activities, and Development as a Functional Food - Varun Jaiswal; Hae-Jeung Lee (Plants)
Graptopetalum paraguayense (G. paraguayense) is a succulent plant that has been used in traditional Chinese and Taiwanese medicine, mainly for antihypertensive and hepatoprotective activities. G. paraguayense is also used as an edible vegetable, which is considered a functional food. Different in vitro, in vivo, and clinical studies have highlighted the multiple pharmacological activities of G. paraguayense, which include anticancer, antibacterial, antiviral, antiasthma, antihypertensive, skin-whitening and anti-aging, anti-Alzheimer, neuroprotective, and hepatoprotective activities. Numerous studies revealed the antioxidant and anti-inflammatory potential of G. paraguayense, which may be the major contributing factor for multiple pharmacological activities and the protective effect of G. paraguayense on pancreatic, liver, lung, colon, and brain diseases. Initial safety studies on animal models also support the therapeutic candidature of G. paraguayense. The presence of numerous bioactive phytochemicals, especially polyphenols, and the identification of important disease targets of G. paraguayense emphasize its high therapeutic potential. The lack of a directional approach and limited in vivo studies limit the development of G. paraguayense against important diseases. Still, a compilation of pharmacological activities and target pathways of G. paraguayense is missing in the literature. The current review not only compiles pharmacological activities and phytochemicals but also highlights gaps and proposes future directions for developing G. paraguayense as a candidate against important diseases.